Pembelajaran Berbasis Inkuiri Berkelompok Untuk Meningkatkan Hasil Belajar Kelas VIII SMPN 1 Tembelang - Zuhriawan, M. Qoyum; Ahmad, Dziqi Jamaludin; Chotimah, Chusnul (JoEMS (Journal of Education and Management Studies), 2024)
Low learning outcomes are often caused by problems in classroom learning activities. One of them is the use of learning media which is limited to printed books, this can reduce student enthusiasm and participation, so that most students become passive. One learning model that is able to overcome this problem is inquiry learning, because it prioritizes the active role of groups. This research aims to explore more about the inquiry learning model in the classroom. This research was conducted in class VIII A of SMPN 1 Tembelang. Using the quantitative experimental method Pretest-Posttest Control Group Design. Learning is carried out in two cycles with stages of planning, implementation, observation and reflection. Data was collected through observing student and teacher learning activities, learning results tests, and documentation. The research results showed a significant increase in student learning outcomes. In cycle I, there were 2 out of 15 students who achieved completeness, in cycle II this increased to 13 students. Based on this research, it can be concluded that the application of group inquiry learning can significantly increase students' motivation and active participation.